Clustering in hybrid environment / Imran Edzereiq Kamarudin - Kamarudin, Imran Edzereiq (Faculty of Information Technology and Quantitative Sciences, 2006)
The cluster, a collection of computers that work together, is an important concept in leveraging computing resources because of its ability to transfer workload from an overloaded system to another system in the cluster. Clusters are not necessarily built by using Linux as the only operating system. Hybrid cluster which is a cluster consisting of heterogeneous operating system is capable of performing cluster operations similar to the ordinary non hybrid cluster. This research concentrates on cluster in hybrid environment. The cluster system is built using at least two machines that have different architecture. It will be tested using sample coding. Not only we will determine the functionality of the cluster, we will also determine which coding is suitable to run on the cluster system The major finding of this study is non hybrid cluster can be done using simple specifications of hardware to perform big computations. While running the cluster agent on Windows based computers using the emulator, it allows users to run any windows-based application concurrently with the cluster agent. In other words, the cluster is doing its job in the background while users can continue working with windows-based applications. This research also finds out which cluster environment between hybrid and non hybrid gives the best results in terms of time processing. The lesser time it takes to complete a process, the better the cluster is. The research concludes with the recommendations to improve future hybrid cluster studies and implementations.